Pengaruh Derajat Keasaman yang Berbeda Terhadap Pertumbuhan Tiga Varietas Selada (Lactuca sativa L.) Hidroponik Sistem NFT - NANIK FUROIDAH; Rahmadi Akbar Ardiansah (Program Studi Agroteknologi, 2026)
Erratic climate conditions cause lettuce production to decline, while the need for lettuce vegetables is increasing. The solution for stable production is hydroponic farming. This study aims to determine the different degrees of acidity that are best for the growth of three varieties of lettuce (Lactuca L). This research was conducted at Pondok Bedadung Indah Housing Block AA. 01 Kelurahan. Tegal Besar, Kaliwates District, Jember Regency, East Java with an altitude of 70 meters above sea level from December 2022 to February 2023. This study used a 3x3 factorial completely randomized design (CRD) with 3 replications. The first factor is lettuce varieties with 3 levels, namely: V1= Anizel lettuce, V2= Butterhead lettuce, and V3= Romain lettuce. The second factor is the degree of acidity with 3 levels, namely D1 = pH 5.5; D2 = pH 6.5; and D3 = pH 7.5. Observation data were analyzed using ANOVA test, if there is a significant difference then continued with Duncan test (DMRT) at 5% level using SPSS 20 for windows. The results showed that the acidity (pH) of 6,5-7.5 solution gave the best response to plant height, number of leaves, root length, and root weight. Romain lettuce varieties provide greater growth and production compared to butterhead lettuce and anizel lettuce on all parameters including plant height, number of leaves, root length, fresh weight, root weight and chlorophyll count. The degree of acidity (pH) solution of 7.5 in romain lettuce plants provides the best growth and production in all observation parameters including plant height, number of leaves, root length, fresh weight, root weight and chlorophyll content.